Entanglement between nodes of a quantum network - Stephenson, L (2019)
Quantum devices are rapidly gaining momentum as a technology that will induce a paradigm shift in computing, communication and cryptography. Trapped ion qubits are one of the leading candidates for implementing a quantum computer, having previously demonstrated all of the required criteria. Local gate fidelities between ions exceed those for all other platforms, but the total number of ions in a trap is limited by unavoidable issues – one possibility for scaling the ion trap quantum processor is to create entanglement between ions in separate traps via single photons. The work in this thesis demonstrates the generation of remote entanglement between ions at high fidelity and rate, paving the way towards protocols using multiple entangled pairs for computations.